Benthic fluxes of oxygen and heat from a seasonally hypoxic region of Saanich Inlet fjord observed by eddy covariance. (30th September 2020) - Reimers, Clare E.; Sanders, Rhea D.; Dewey, Richard; Noel, Rick
Abstract: Benthic habitats within fjords are predominantly insulated from the high energy physical dynamics of open coastlines. As a result, fjords may have atypical mass and heat transfer rates at the seafloor. This study presents aquatic eddy covariance (EC) measurements made continuously from late May 2013 through December 2013, in Saanich Inlet fjord, British Columbia, to assess areal-averaged benthic fluxes of dissolved oxygen and heat, and their relationships to bottom boundary layer dynamics and water properties. The measurements were achieved by the connection of a system of underwater EC sensors to Ocean Network Canada's Victoria Experimental Network Under the Sea (VENUS) observatory that has a primary seafloor node located near the 100-m isobath in Patricia Bay off the eastern shore of Saanich Inlet. Current velocities and turbulence (characterized by turbulent kinetic energy and dissipation rate estimates) were observed to be generally low with the weakest dynamics in autumn during periods of heightened hypoxia. EC fluxes that represented turbulent eddy transport in balance with the seafloor source/sink were derived through conditional criteria that excluded measurements occurring when the bottom boundary layer was not sufficiently turbulent or when transient shifts in bottom water properties were observed. The accepted fluxes of oxygen (−1.6 ± 1.2 mmol m −2 d −1 ) and heat (0.27 ± 0.57 W m −2 ) showed only modest variations within the observed 7-month period in Saanich Inlet. Broader implications of these fluxes are that: 1) seafloor oxygen uptake rates are too limited to drive annual expansions and intensification of the site's overlying seasonal hypoxic zone, and 2) heat transferred to the seabed in summer is only slowly dissipated back to the water column during other times of the year. Highlights: Aquatic eddy covariance was applied from a seafloor observatory. Benthic fluxes of dissolved oxygen and heat were assessed over a 222-day period. The study site was in a region of recurring hypoxia and low turbulence. Benthic oxygen demand was too limited to drive the seasonal expansion of hypoxia. Heat fluxes responded to changes in bottom water temperature.